Correlates and Trajectories of Preterm Infant Sucking Patterns and Sucking Organization at Term Age. (April 2021) - McGrath, Jacqueline M.; Bromiker, Ruben; Hanlon, Alex; McGlothen-Bell, Kelly; Medoff-Cooper, Barbara
Abstract : Background: Premature infants may experience increased difficulty with nutrition and growth. Successful oral feeding is an important factor associated with discharge readiness. Despite the importance of feeding as a growth-fostering process, little empiric evidence exists to guide recommendations for early interventions. Purpose: Evaluate whether specific elements of sucking, during preterm initiation of oral feeding, predict sucking organization at corrected term age. Methods: Sucking performance of 88 preterm infants born between 24 and 34 weeks of post–menstrual age was measured at baseline and term (33-35 and 40 ± 1.5 weeks). Participants were divided into 4 groups (quartiles) based on initial measures of performance including number of sucks, number of bursts, sucks per burst, and maximum pressure. Stability in sucking organization was assessed by comparing changes in infant's quartile location from baseline to term. Results: A correlation between quartile location was observed for mean maximum pressure (PMAX): infants with PMAX in the lowest quartile (poorest performance) were significantly more likely to remain in the lowest quartile at term ( P < .000); infants in the highest quartile (best performance) at baseline were significantly more likely to be in the highest quartile at term ( P < .000). Implication for Practice: Infants with the weakest sucking pressures at 34 weeks of post–menstrual age continue to be at risk for less than optimal feeding skills at 40 weeks of post–menstrual age. Early identification of at-risk infants may allow for effective interventions to potentially decrease long-term feeding problems. Implications for Research: Future research should focus on the development of personalized interventions to address attributes of problematic feeding such as sucking efficiency.